Support Group Intervention on Self-Awareness and Parental Coping Strategies as an Effort to Prevent Sexual Violence in Children - Laili, Nurul; Hasanah, Yulia Rahmawati; Handayani, Erna (Journal of Applied Nursing and Health, 2023)
Background: The victims, primarily female children, have suffered sexual abuse, often perpetrated by individuals known to them, such as neighbors or acquaintances. In interviews with concerned parents regarding ongoing cases of sexual abuse, they expressed fears about their children falling victim to such incidents.. The research aim was to assess the effectiveness of support group interventions in enhancing self-awareness and parental coping strategies as preventive measures against child sexual abuse. Methods: The study's main objective is to evaluate the impact of Support Groups in improving Self-Awareness and Parental Coping Strategies. It employed a quasi-experimental design using a non-equivalent group pre-test and post-test methodology, with one group as the control and the other as the experimental group. The study included 70 respondents in the intervention group and an equal number in the control group, selected through purposive sampling. Research instruments comprised the Revised Ways of Coping Scale questionnaire for coping strategies and a self-awareness questionnaire. Non-parametric data analysis was conducted using SPSS, specifically the Wilcoxon Signed Rank Test. Results: Results of the normality test indicated that both the intervention and control groups had p-values of less than 0.05 for coping strategies (0.002 for the intervention group and 0.003 for the control group) and self-awareness (0.000 for both groups), suggesting non-normal data distribution. Consequently, non-parametric statistical analysis was applied with SPSS, and a significance level was set at p < 0.05. The Wilcoxon Signed Rank Test results for the intervention group were 0.000 (coping strategies) and 0.000 (self-awareness), signifying a significant difference in average pretest and posttest scores within the intervention group. Conversely, the control group's Wilcoxon Signed Rank Test results were 0.953 (coping strategies) and 0.317 (self-awareness), indicating no significant difference in average pretest and posttest scores within the control group. Conclusion: Based on the research findings and discussion, it can be deduced that support group interventions positively impact the enhancement of parental coping strategies and self-awareness in the endeavor to prevent child sexual abuse.